Pregnancy-associated spontaneous coronary artery dissection: a challenging scenario in limited-resource setting - Abdullah, Hassan; Ayesha Rafique; Asad Jamil Awan; Muhammad Muzaffar Mahmood (Journal of the Pakistan Medical Association, 2025)
Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome (ACS). We report a case of SCAD in a patient who had her Caesarean section three weeks earlier. This report describes the management, emphasising the need to keep a high index of suspicion to avoid mismanagement, such as inadvertent thrombolysis which may prove disastrous in such situations. The practical aspects of performing percutaneous coronary intervention in patients with SCAD are also discussed. MeSH Key: Acute Coronary Syndrome, Coronary Vessels, Percutaneous Coronary Intervention, Thrombolytic Therapy, Caesarean Section.